Computer-Aided Rehabilitation of Maxillary Oncological Defects Using Zygomatic Implants: A Defect-Based Classification. - Pellegrino, Gerardo; Tarsitano, Achille; Basile, Francesco; Pizzigallo, Angelo; Marchetti, Claudio (Journal of Oral & Maxillofacial Surgery (02782391), 2015)
Purpose: A complete maxillectomy for neoplastic lesions leads to serious oral dysfunction. Zygomatic implants for fixed bridge support are considered beneficial for maxillary defects after tumor resection.Materials and Methods: This clinical study examined the management of patients with different maxillary defect types who underwent delayed rehabilitation using zygomatic implants and immediate prosthetic loading. Virtual preoperative planning and intraoperative navigation were performed in all cases.Results: Five patients were treated with this new method. The total number of zygomatic implants positioned was 17. Four patients had immediate loading of a fixed prosthesis and 1 had delayed loading. One patient had 1 failed implant.Conclusion: The use of preoperative virtual surgical planning and an intraoperative navigation system allows the surgeon to achieve safer implant positioning in a complex anatomic site. A systematic bone defect classification was created and a specific treatment protocol is proposed for each type of defect.